Vaccines for all? A rapid scoping review of COVID-19 vaccine access for Venezuelan migrants in Latin America - Amaya Perez-Brumer (Elsevier, 2021)
Introduction: The entangled health and economic crises fueled by COVID-19 have exacerbated the challenges facing Venezuelan migrants. There are more than 5.6 million Venezuelan migrants globally and almost 80% reside throughout Latin America. Given the growing number of Venezuelan migrants and COVID-19 vulnerability, this rapid scoping review examined how Venezuelan migrants are considered in Latin American COVID-19 vaccination strategies. Material and Methods: We conducted a three-phased rapid scoping review of documents published until June 18, 2021: Peer-reviewed literature search yielded 142 results and 13 articles included in analysis; Gray literature screen resulted in 68 publications for full-text review and 37 were included; and official Ministry of Health policies in Argentina, Brazil, Chile, Colombia, Ecuador, and Peru were reviewed. Guided by Latin American Social Medicine (LASM) approach, our analysis situates national COVID-19 vaccination policies within broader understandings of health and disease as affected by social and political conditions. Results: Results revealed a heterogeneous and shifting policy landscape amid the COVID-19 pandemic which strongly juxtaposed calls to action evidenced in literature. Factors limiting COVID-19 vaccine access included: tensions around terminologies; ambiguous national and regional vaccine policies; and pervasive stigmatization of migrants. Conclusions: Findings presented underscore the extreme complexity and associated variability of providing access to COVID-19 vaccines for Venezuelan migrants across Latin America. By querying the timely question of how migrants and specifically Venezuelan migrants access vaccinations findings contribute to efforts to both more equitably respond to COVID-19 and prepare for future pandemics in the context of displaced populations. These are intersectional and evolving crises and attention must also be drawn to the magnitude of Venezuelan mass migration and the devastating impact of COVID-19 in the region. Integration of Venezuelan migrants into Latin American vaccination strategies is not only a matter of social justice, but also a pragmatic public health strategy necessary to stop COVID-19.